2018
DOI: 10.3390/w10111516
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Precipitation Simulations in Central Asia by CMIP5 Climate Models

Abstract: The Coupled Model Intercomparison Project Phase 5 (CMIP5) provides data, which is widely used to assess global and regional climate change. In this study, we evaluated the ability of 37 global climate models (GCMs) of CMIP5 to simulate historical precipitation in Central Asia (CA). The relative root mean square error (RRMSE), spatial correlation coefficient, and Kling-Gupta efficiency (KGE) were used as criteria for evaluation. The precipitation simulation results of GCMs were compared with the Climatic Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…As climate simulations remain uncertain, there is a need to examine the possible changes in maize biomass under different climate scenario models to obtain a reliable fluctuation range for future projections of maize biomass yields. Based on previous studies in the Xinjiang area, the CGCM3 and NORESM models can accurately simulate changes in temperature [36], while the MIROC5 model can predict changes in precipitation very well [42,43]. Based on the accuracy of these three climate models for our study area, we used the CGC3M, NORESM, and MIROC5 to drive the DNDC model and found that the maize biomass yield fluctuates between −6.5% and 10.3% compared to the baseline scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…As climate simulations remain uncertain, there is a need to examine the possible changes in maize biomass under different climate scenario models to obtain a reliable fluctuation range for future projections of maize biomass yields. Based on previous studies in the Xinjiang area, the CGCM3 and NORESM models can accurately simulate changes in temperature [36], while the MIROC5 model can predict changes in precipitation very well [42,43]. Based on the accuracy of these three climate models for our study area, we used the CGC3M, NORESM, and MIROC5 to drive the DNDC model and found that the maize biomass yield fluctuates between −6.5% and 10.3% compared to the baseline scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…But highest improvement not necessarily mean the highest performance of model, rather it is the change in the skill of a given model before and after the correction. Actually, model performance depends on various factors such as, variables affecting earth-climate interaction, geographical locations (Choi et al, 2016;Purwaningsih and Hidayat, 2016;Homsi et al, 2020), spatial resolution of model structure (Lovino et al, 2018;Jain et al, 2019), temporal resolution of simulating variables and spatial and temporal scale of the considered variables (Sheffield et al, 2013;Ta et al, 2018). Comparison of model performances of different categories (as identified in this study) revealed that the models in category-I are more skilful than models in category-II for decadal hindcast precipitation.…”
Section: Discussionmentioning
confidence: 71%
“…The SWAT model has been applied in several hydrological modeling studies in various catchments around the world [14,25,97]. There may be a few areas of uncertainty in modeling snow and glacier melt, such as orographic impacts and hydrological model parameterization, as well as heterogeneity in forest cover, slope, and features, which are evident issues in snow and glacier hydrology.…”
Section: Uncertainties and Limitationsmentioning
confidence: 99%